I-aeroponic system / Siti Afiqah Selamat, Siti Hawa Mohammad and Siti Norsyafiqah Hambali - Selamat, Siti Afiqah; Mohammad, Siti Hawa; Hambali, Siti Norsyafiqah (2015)
This project presents about the new idea of watering plant process that using aeroponics planting method. This project uses the automatic watering method that responds with humidity in the plant medium. There are two circuits involved in this project which are humidity sensor circuit and water level circuit. Humidity sensor is used to detect the humidity of plant in aeroponics plants medium and then connects to the circuit which controls the water pump. This process happens when humidity in aeroponics plants medium decreases and turns on the circuit by the switch that will on the water pump. Water will be pumped up from the tank and spray the plant’s roots by using sprinkler. Next circuit is to control the level of water in the tank to avoid overflowing. If the water in the tank decreases below the water sensor, the water pump will pump up the water into the tank until the water reaches the sensor and the pumping process will stop immediately. Therefore, there will be no problems of water lacking or overflowing of water in the water tank. This project is an automatic process. So, the process of planting becomes more easier.